TINGKAT KECEMASAN PASIEN SEBELUM DAN SESUDAH PEMBEDAHAN DI RUMAH SAKIT SWASTA YOGYAKARTA - Titin Marlina, Theresia (MEDIA ILMU KESEHATAN, 2017)
Background: Surgery is a major stressor for most patients. Preoperative anxiety determines the success or failure of surgery and recovery, as well as postoperative anxiety. The role of the nurses are very important in assessing the patient's anxiety. The giving of information about surgery and post-surgery manajemen are needed the patients. Objective: The aims of this study is to determine the level of patients anxiety before and after surgery Methodes:This research is non experimental with cross sectional design. The population is all patients undergoing surgery, with a sample of 80 patients by accidental sampling. The instrument is HARS (Halmington Anxiety Rating Scala). Data collection on April 2015. Beginning with inform concent and then giving quisioner to patients. The questionnaires were administered before surgery and after the patients had surgery. Univariate analysis and paired t test are the analysis used. Results: Middle anxiety levels before surgery are 45% to 25% after surgery. Mild anxiety levels before surgery are 34% to 10% after surgery. While the respondents who did not anxiety before surgery are 10% to 61,25% after surgery. Conclusion: There was a significant difference in the patients anxiety levels before and after surgery with p= 0,00. Keywords : Anxiety, surgery, role of the nurses